G490(P) Neuroprotective benefit of antenatal magnesium sulfate for preterm infants. Is it the magnesium or the sulfate?. (24th May 2017) - Hurrion, EM; Colditz, PB; Boyd, RN; Badawi, N; Koorts, PJ; Kumar, S; Flenady, VJ; Dawson, PA
Abstract : Aims: To determine whether antenatal magnesium sulfate (MgSO4 ) administration correlates with circulating sulfate level in very/extremely preterm infants, and specifically whether non-exposed infants become sulphate deficient. Methods: Ion chromatography was used to measure plasma sulfate levels in preterm infants (<32 wk gestation) whose mothers did or did not receive antenatal MgSO4 . Results: Within 24 hours after birth, supra-physiological plasma sulfate levels were measured in infants whose mothers received MgSO4 (mean±SD mmol/L 774±397, n=26), whereas sulfate levels in the group without MgSO4 (257±162, n=10) were similar to that found in term cord blood. At 3 days and at 1 and 4 weeks of age, babies without antenatal MgSO4 had reduced plasma sulfate level (3d: 190±96, n=49; 1 wk 118±61, n=67; 4 wk 125±79, n=6) whereas the group with antenatal MgSO4 therapy maintained normal levels (3d: 287±160, n=68; 1 wk 250±125, n=119; 4 wk 228±89, n=56). Conclusions: These data positively correlate antenatal MgSO4 administration with neonatal plasma sulfate levels, and suggest that unexposed preterm infants (who lack the capacity to generate sulphate) rapidly become sulphate depleted. Animal models and human studies demonstrate that sulphate is important for modulating brain development. It may be, therefore, that the neuroprotective benefit of antenatal MgSO4 for preterm infants is attributable to the sulphate rather than the magnesium content. If sulfate neuroprotection is proven, then neonatal sulfate supplementation (in place of antenatal MgSO4 ) may prove a simple and effective, low-cost, low-risk intervention universally available to all preterm infants to improve their chances of a normal neurodevelopmental outcome.